(untitled) - 1959-; Shannon, David (New York, 2002)
A duck decides to ride a bike and soon influences all the other animals on the farm to ride bikes too.
Keywords: Ducks; Fiction; Domestic animals; Fiction; Bicycles and bicycling; Fiction